Viscosity of hot-melts adhesives based on vinyl acetate copolymers - Machač, Ivan; Šiška, Bedřich; Balcar, Miroslav; Vrána, Jiří (University of Pardubice, 2015)
In this paper, the results of measurements are presented concerning the shear viscosities in the dependence on temperature of five hot melts adhesives based on polyvinyl acetate – polyethylene copolymers EVAK. Using the viscosity data measured, the accuracy of three blending models, reported in the literature for multicomponent blends, was tested for viscosity predicting. It has been found that no model was capable to estimate satisfactorily the adhesive melt viscosity in the whole interval of the temperature examined. To achieve a higher accuracy of viscosity estimation, it is necessary to incorporate into models a corrective function of temperature.